2010
DOI: 10.1590/s0104-11692010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk donation and social support: reports of women donors

Abstract: The study aimed to characterize the behavior of human milk donation and to describe the informal social and formal institutional support, according to reports from women donors.It is an exploratory, cross-sectional, descriptive study using domicile interviews based on structured and semi-structured scripts. The participants were 36 women enrolled in two human milk banks of the public health system of the Federal District. Statistical analysis of quantitative data and categorical content analysis of qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 10 publications
1
22
0
6
Order By: Relevance
“…The absence of feedback to donors about the need for and outcome of banked donor milk is a barrier to donation that could be overcome. Previous research has found that milk bank donors would like to know more about what happens to their milk after donation including who receives the milk, why the milk is needed, and why the infant's mother is unable to provide milk (De Alencar & Seidl, ). Milk banks have historically followed organ donation policy in maintaining anonymity and not providing donors with information about how their milk is used.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of feedback to donors about the need for and outcome of banked donor milk is a barrier to donation that could be overcome. Previous research has found that milk bank donors would like to know more about what happens to their milk after donation including who receives the milk, why the milk is needed, and why the infant's mother is unable to provide milk (De Alencar & Seidl, ). Milk banks have historically followed organ donation policy in maintaining anonymity and not providing donors with information about how their milk is used.…”
Section: Discussionmentioning
confidence: 99%
“…In Alencar et al 17 study, altruism is reported by most women as the main reason for donation, which diverges from the current outcome. According to the present study, the fact that the woman had previously received milk for another child or that had already donated the milk to the HMB did not show statistically significant relation with a new donation, human milk, similar in comparing groups, which would facilitate the planning and dissemination of campaigns to stimulate human milk donation promoted by the HMB, aiming to receive new donors and to increase human milk supplies.…”
Section: Variablesmentioning
confidence: 56%
“…1,[17][18][19][20] However, no studies were found that specifically relate to the donor's PCI for each reason to donate, making this present study the pioneer on this context.…”
Section: Discussionmentioning
confidence: 99%
“…O referido autor compreende o apoio social como a informação que proporciona ao indivíduo acreditar que há pessoas que o amam, o estimam, o valorizam e que ele faz parte de uma rede de comunicação e obrigação recíproca. Trata-se de um conceito que tem sido bastante utilizado em pesquisas que investigaram este tema (Alencar & Seidl, 2010;Guimarães & Melo, 2011). Ademais, a forma de avaliação utilizada neste trabalho tem como base o apoio social percebido por cada indivíduo (Sherbourne & Stewart, 1991).…”
Section: Introductionunclassified